PENGARUH KONSENTRASI DAN LAMA FERMENTASI LIMBAH BUAH DAN SAYURAN TERHADAP PERTUMBUHAN DAN PEMBUNGAAN MAWAR (Rosa sp) VARIETAS baby rose - Siska Rahayu; Armaini Armaini; Isna Rahma Dini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of concentration and fermentation durationand the best concentration at each fermentation time of fruit and vegetable waste to rose varieties baby rose, conducted inthe Facultyof Agricultur, Riau University from April to July 2017. This research using a randomized block design (RAK) consisting of two factors and three replications. The first factor was the concentration of fermented fruit and vegetable waste with five levels, i.e. 0 ml.l-1 water,  5 ml.l-1 water, 10 ml.l-1 water, 15 ml. l-1 water and 20 ml. l-1 water. The second factor was the duration of fermentation fruit and vegetable waste with of three levels, namely 10 days of fermentation, 20 days fermentation and 30 days of fermentation. Parameters measured were the number of crop shoots, shoot length, when the first flowers appear, flower stem length, petal number and the number of florets crop planting. The results showed that the concentration wastes fermented fruits and vegetables can increase the number of shoots per plant, shoot length, when the first flowers appear, flower stem length, diameter flowers bloom, petal number per florets and the number of buds per plant. Treatment concentrations of 5-20 ml.l-1 water better than the treatment 0 ml.l-1 water. Treatment of 5ml.l-1water is the best treatment to increase the number of florets per plant, while the fermentation treatment does not give effect to all parameters. Treatment concentrations of 5 ml.l-1 water on a long fermentation 10, 20 and 30 days is the best treatment to increase the number of florets per plant. Keywords: roses, concentration, fermentation